Bioautographic Analysis And Antibacterial Activity Test Of Curry Leaf (Murraya Koenigii (L) Spreng) Ethanol Extract On The Bacteria Propionibacterium Acnes - Muhammad Wahyu Ikhsan Muhammad Wahyu Ikhsan; Haris Munandar Nasution; Yayuk Putri Rahayu; M. Pandapotan Nasution (International Journal of Health and Pharmaceutical (IJHP), 2022)
Curry leaf (Murraya koenigii (L) Spreng) is one of the plants known to have antibacterial compounds. Curry leaves are also known as temurui leaves and are useful as a natural food flavoring. Curry leaves contain flavonoid compounds, alkaloids, calcium, zinc, riboflavin, folic acid. This study aimed to analyze the bioautography and antibacterial activity of ethanol extract of curry leaves against Propionibacterium acnes bacteria. The research method was carried out experimentally. Curry leaf simplicia extract was made with 96% ethanol as solvent. Curry leaf ethanol extract was made in various concentrations, namely 30%, 40% and 50%. The positive control used was Tetracycline HCl and the negative control was DMSO. The tests carried out on curry leaf simplicia included phytochemical screening, macroscopic examination, microscopic examination, water content examination, examination of water soluble extract content, examination of ethanol soluble extract content, examination of ash content and examination of acid insoluble ash content, bioautographic analysis he results of phytochemical screening showed that curry leaves contain secondary metabolites, namely flavonoids, alkaloids, tannins, saponins, steroids/triterpenoids, and glycosides. The results of the antibacterial activity showed that curry leaves could be used as antibacterial because they had strong inhibition at concentrations of 30%, 40% and 50%, namely 10.3 mm, 11.7 mm and 13.6 mm against P. acnes bacteria. The results of bioatuography showed that the Rf value in the clear zone was 0.17 with a ratio of chloroform:n-Hexane (8:2) on the chromatogram spots by spraying 10% FeCl3 positive for flavonoid compounds which were marked in black.